KEKUATAN HUKUM AKTA JUAL BELI ATAS PENJUALAN HARTA BERSAMA YANG TANPA PERSETUJUAN SALAH SATU PIHAK DARI MANTAN SUAMI ATAU MANTAN ISTRI (Studi Putusan Nomor 3200/Pdt.G/2016/PA.Lmj.) - Andik Wicaksono (Legal Spirit, 2020)
Joint property is property acquired during the marriage (article 35 paragraph (1) of law number 1 Year 1974), the acquisition of such property involves the role as well as husband and wife, both roles as well as directly or indirectly. When one party ex-husband or ex-wife sell along the treasure without the consent and knowledge of the ex-husband or ex-wife then the sale is not valid and does not have the force of law (Religious Court ruling of Lumajang Number 3200/Pdt.G/2016/PA. Lmj.). TER Haar says. "... goods acquired during marriage by husband and wife is a treasure together so it is a treasure (as part of the family treasures) that at the time of happening of something (especially divorce) gives rise to the right of the husband and wife over the treasure (each part). The absence of shared property, is a penegecualian. Only on patrineal societies, then the existence of the treasure family husband (on mating honest) or property wife (on the mating semendo) does not provide the possibility of the formation of the joint property, regardless of how small the possibility ".